Study protocol for the targeting effective analgesia in clinics for HIV (TEACH) study – a cluster randomized controlled trial and parallel cohort to increase guideline concordant care for long-term opioid therapy among people living with HIV. Issue 2 (26th April 2019) - Lira, Marlene C.; Tsui, Judith I.; Liebschutz, Jane M.; Colasanti, Jonathan; Root, Christin; Cheng, Debbie M.; Walley, Alexander Y.; Sullivan, Meg; Shanahan, Christopher; O'Connor, Kristen; Abrams, Catherine; Forman, Leah S.; et al.
Abstract : Background : People living with HIV (PLWH) frequently experience chronic pain and receive long-term opioid therapy (LTOT). Adherence to opioid prescribing guidelines among their providers is suboptimal. Objective : This paper describes the protocol of a cluster randomized trial, targeting effective analgesia in clinics for HIV (TEACH), which tested a collaborative care intervention to increase guideline-concordant care for LTOT among PLWH. Methods : HIV physicians and advanced practice providers ( n = 41) were recruited from September 2015 to December 2016 from two HIV clinics in Boston and Atlanta. Patients receiving LTOT from participating providers were enrolled through a waiver of informed consent ( n = 187). After baseline assessment, providers were randomized to the control group or the year-long TEACH intervention involving: (1) a nurse care manager and electronic registry to assist with patient management; (2) opioid education and academic detailing; and (3) facilitated access to addiction specialists. Randomization was stratified by site and LTOT patient volume. Primary outcomes (≥2 urine drug tests, early refills, provider satisfaction) were collected at 12 months. In parallel, PLWH receiving LTOT ( n = 170) were recruited into a longitudinal cohort at both clinics and underwent baseline and 12-month assessments. Secondary outcomes were obtained through patient self-report among participants enrolled in both the cohort and the RCT ( n = 117). Conclusions : TEACH will report the effects of an intervention on opioid prescribing for chronic pain on both provider and patient-level outcomes. The results may inform delivery of care for PLWH on LTOT for chronic pain at a time when opioid practices are being questioned in the US. Trial registration: ClinicalTrials.gov identifier: NCT02564341. Trial registration: ClinicalTrials.gov identifier: NCT02525731.